Learning assessment and value-added scores in the national surveys for the first cycle of schooling - Davide Capperucci (Firenze University Press, 2017)
This present paper examines the value-added scores of National Evaluation Service surveys for the two-year period 2015-2017. Moving from the international debate on regression statistical models and the degree of reliability of the value-added assessment for school learning, the article investigates how the so-called "school effect" can be detected and supported in the practice of schools starting from the result analysis of national evaluation surveys. In doing so, the strengths and weaknesses of the value-added measures used both in the system and school evaluation are highlighted, in support of the thesis that such procedures may prove useful not so much in building external accountability systems than to the promotion of internal self-assessment processes aimed at increasing the effectiveness of teaching and improving the performance of pupils.   Valutazione degli apprendimenti e calcolo del valore aggiunto nelle rilevazioni nazionali per il primo ciclo d'istruzione Il presente contributo prende in esame la misura del valore aggiunto nelle rilevazioni del Servizio Nazionale di Valutazione in riferimento al biennio 2015-2017. A partire dal dibattito internazionale sui modelli statistici di regressione e sul grado di affidabilità del valore aggiunto applicato alla valutazione degli apprendimenti, viene indagato in che modo il cosiddetto "effetto scuola" possa essere rilevato e supportato nella pratica delle scuole a partire dall'analisi dei risultati delle rilevazioni nazionali. Nel fare questo vengono messi in luce i punti di forza e di debolezza delle misure del valore aggiunto impiegate sia nella valutazione di sistema che in quella delle scuole, a sostegno della tesi che dette procedure possono rivelarsi utili non tanto alla costruzione di sistemi esterni di accountability quanto alla promozione di processi interni di autovalutazione finalizzati all'elevamento dell'efficacia didattica e al miglioramento delle prestazioni degli alunni.